2015
DOI: 10.1371/journal.pone.0142012
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of Mineralocorticoid Receptors Partially Prevents Chronic Stress-Induced Reductions in Hippocampal Memory and Structural Plasticity

Abstract: Exposure to chronic stress is a risk factor for cognitive decline and psychopathology in genetically predisposed individuals. Preliminary evidence in humans suggests that mineralocorticoid receptors (MRs) may confer resilience to these stress-related changes. We specifically tested this idea using a well-controlled mouse model for chronic stress in combination with transgenic MR overexpression in the forebrain. Exposure to unpredictable stressors for 21 days in adulthood reduced learning and memory formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 70 publications
(102 reference statements)
3
28
1
Order By: Relevance
“…We observed that MR overexpressing females were heavier at 4 months of age when compared to control animals, a finding we observed before at the age of 3 months old, both in female (Kanatsou et al, 2015a ) and male animals (Kanatsou et al, 2015b ). A previous study showed that mice with MR deletion in the forebrain have a reduced bodyweight (Ter Horst et al, 2012 ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We observed that MR overexpressing females were heavier at 4 months of age when compared to control animals, a finding we observed before at the age of 3 months old, both in female (Kanatsou et al, 2015a ) and male animals (Kanatsou et al, 2015b ). A previous study showed that mice with MR deletion in the forebrain have a reduced bodyweight (Ter Horst et al, 2012 ).…”
Section: Discussionsupporting
confidence: 75%
“…All mice were bred in-house by crossing male MR-tg mice with C57BL/6J females. One male animal was housed for 1 week with two female mice (Kanatsou et al, 2015a , b ). The mouse line with forebrain MR overexpression (MR-tg) was generated by inserting the HA-tagged human MR cDNA using the CamKIIα promoter (Lai et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MR overexpression restored the reduced learning in the low arousing task only. This change in behaviour was paralleled by normalisation of the chronic stress‐induced reductions in neurogenesis observed in the infrapyramidal blade of the dentate gyrus . The finding agrees with a previous study by Ferguson and Sapolsky conducted in rats involving viral overexpression of MR in the dentate gyrus.…”
Section: Translational Studiesmentioning
confidence: 92%
“…The idea that increased hippocampal MR may provide resilience was tested further in MR hi mice exposed for 3 weeks daily to an unpredictable stress paradigm , mimicking the chronic stress conditions that predispose humans to depression. In wild‐type mice, such a chronic stress experience reduced learning in a low arousing hippocampus contextual learning task but enhanced stressful contextual learning.…”
Section: Translational Studiesmentioning
confidence: 99%